Tipologi Pedogeomorfik Longsorlahan di Pegunungan Menoreh Kabupaten Kulonprogo Daerah Istimewa Yogyakarta - Priyono, Kuswaji Dwi; Sunarto, S; Sartohadi, Junun; Sudibyakto, S (Universitas Muhammadiyah Surakarta, 2011)
Pedogeomorphology tipology was applied in this research to determine the occurrence of landslide in the Menoreh Mountains, Kulonprogo District, Yogyakarta Special Region. The research aimed to know (1) soil characteristics where landslide events occurred in the research area, (2) characteristic of landslide prone landform in the research area, and (3) typology pedogeomorphic of landslide events in the research area. Pedogeomorphologic approach was represented through the steps of mapping the occurrence of landslides and landform, soil profile pedogenitic analysis and geomorphologic analysis at the point of occurrence of landslide. The results show that landforms characteristic on the occurrence of landslide with slope 16-75%, elevation 210-807 m dpal, weathered zone depth 25-80 cm, and the position of contacts on the opposite slope is flat and parallel. The soil characteristics on the occurrences of landslides have a 20-186 cm soil depts with the content 21,50-95,00% of caolinite clay, and clay content ratio between horion A dan B 0,22-0,91. Pedogeomorphic typology landslides prone classified into 3 levels, namely: low, moderate, and high level of vulnerability. The low level are indicated by the thickness of soil depth 0,60, slope < 25%, elevation 120 cm, caolinite clay content >70%, clay content ratio of A and B horizon < 0,40, slope >60%, elevation >600 m dpal, the depth of weathered zone > 60 cm, and the position of field contact against the slopes is parallel.